The Activity of Antimicrobial Peptides in Pediatric Celiac Disease - Kamilova, Altinoy T.; Azizova, Gulnoza K.; Umarnazarova, Zulkhumar E.; Abdullaeva, Dilrabo A.; Geller, Svetlana I. (Frontiers in Pediatrics, 2022)
Background: Celiac disease (CD) is an immune-mediated disorder of the gut in which innate and adaptive responses are involved. Antimicrobial peptides (AMPs) constitute an arsenal of innate immunity regulators of paramount importance in the gut. However, the role of AMPs in CD is unclear. Aims: To evaluate the levels of fecal β-defensin-2, fecal calprotectin (FC), and antibodies against bactericidal/permeability-increasing protein (BPI) in the serum of children with active CD and to compare them with those of healthy controls (HC). Methods: We examined 76 children with recently diagnosed CD between the age of 2 to 10 years (average age: 6.1 ± 1.2 years) and 32 HC in this study. Fecal β-defensin-2 and FC levels were measured using an enzyme-linked immunosorbent assay (ELISA) kit, and the level of anti-BPI antibodies was determined in the serum using an chemiluminescent immunoassay (CLIA) kit. Correlation relationships between the parameters were assessed according to Pearson correlation coefficient. Results: β-defensin-2 concentration was greater in the CD group than in HC group, amounting to 99.6 ± 15.5 ng/mL and 64.0 ± 2.4 ng/mL, respectively (p<0.02). The level of FC in the CD children was 35.4 ± 8.1 μg/g , while that in the control group was 19.1 ± 1.1 μg/g, (p<0.05), representing an insignificant increase. The concentration of anti-BPI antibodies in the CD and HC groups was 35.9 ± 10.1 U/mL and 5.2 ± 3.2 U/mL, respectively (p<0.001). There was a strong and direct correlation between fecal β-defensin-2 and fecal calprotectin (r = 0.69), as well as a direct but weak relationship between fecal β-defensin-2 and anti-BPI antibodies (r = 0.35). Conclusions: Our data reinforce that fecal β-defensin-2 and anti-BPI antibodies are greatly increased in patients with active CD. These biomarkers may be components of epithelial innate immunity in the intestine, with each having a distinct functional role in intestinal mucosal defense.